Outcomes of CCAFS Work in the Philippines - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
With a number of activities in the Philippines, an outcome assessment of CCAFS work in the country was conducted. The goal of the study is to see how the CCAFS SEA outputs contributed to the agriculture-related policies and programs implemented by the Philippine government. Looking at the development outcomes in the agriculture sector of the Philippines, this paper identified, described, verified, and analyzed changes with respect to climate change-related knowledge, attitude, capacity, policy or practice of the CCAFS SEA stakeholders in the country. Although Philippines is not a priority country of CCAFS, there is still a lot of significant works done in the country, producing a range of outcomes.